2020
DOI: 10.21831/hsjpi.v7i2.31686
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology studies in junior high school students' enthusiasm in social studies learning in Universitas Malang Laboratorium, Indonesia

Abstract: Social science is a common subject given at every level of education. The Social Sciences junior high school curriculum is taught in an integrated manner to facilitate students' social science learning that is important in everyday life. Unfortunately, there are many obstacles encountered in social studies in practice, one of which is the lack of interest and enthusiasm of students in learning social studies. It makes students unable to grasp the importance of social studies. This research conduct on students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, Ceylan and Kesici (2017) mentioned that students who participated in distance education had better academic scores than students in traditional classes. Meanwhile, students also encountered issues such as a lack of knowledge of the LMS (Gillis & Krull, 2020), distractions at home (Tu & Luong, 2021), lack of interest to answer activities in the modules (Wijanarko et al, 2020), and the inability to pay attention to their virtual classes during the pandemic. Furthermore, Abdullah et al (2021) asserted that the COVID-19 lockdown had various negative effects on mental health, including feelings of isolation, despair, anxiety, and among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Ceylan and Kesici (2017) mentioned that students who participated in distance education had better academic scores than students in traditional classes. Meanwhile, students also encountered issues such as a lack of knowledge of the LMS (Gillis & Krull, 2020), distractions at home (Tu & Luong, 2021), lack of interest to answer activities in the modules (Wijanarko et al, 2020), and the inability to pay attention to their virtual classes during the pandemic. Furthermore, Abdullah et al (2021) asserted that the COVID-19 lockdown had various negative effects on mental health, including feelings of isolation, despair, anxiety, and among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Visual media will help in the lesson because it can help motivate students and boost their enthusiasm to learn. This especially becomes important as Wijanarko (2020) found that junior high school students often show unenthusiastic behavior when learning, leading them to do other things that are not related to the learning process, such as chatting, joking with friends, drawing, and so on.…”
Section: Introductionmentioning
confidence: 99%